Tatak Pilipino [episode no. 51]. ([Quezon City ABS-CBN, 1991)
A unique display of Pilipino ways and style.
Historical rap calendar of December (5 min.) -- Chefs om parade, 1991 (3 min.) -- Spiritual series of U. F. O. (3 min.) -- Chefs on parade-Butter sculpture (3 min.) -- Children's Rehabilitation Center (10 min.) -- Chefs on parade-Butter sculpture (2 min.) -- Corridor (10 min.) -- 97 years. of Philippine carols (10 mon.) -- Chefs on parade -- Vegetable sculpture (2 min.)
In English and Pilipino.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Unidentified flying objects; Garnishes (Cookery).; Carols -- Philippines; Lambanog; Philippines -- History